Modern day groit on ancient African accomplishment (Historia, 2021)
Christopher Ehret has been writing African history from a linguistic perspective since the 1960’s. As a young historian he was involved in one of the major formative periods in the development of the new academic African historiographical tradition that followed in the wake of the continental drift towards decolonisation. At the time, the Journal of African History was making its mark as a major scholarly platform for airing superlative work by a few interdisciplinary historians who had gone well beyond merely exploring the avenues of anthropology, archaeology and political history in isolation from each other. They had in fact started opening up the histories of a rich, colourful and vibrant continent. There was a wealth of knowledge that had hardly beentapped.
Keywords: African history; linguistic perspective; historiographical tradition; anthropology; archaeology; political history; Philosophy of History; World History